Analysis of Nurse Job Satisfaction and its Associated Factors in the Hospital Inpatient Room - Rischa Hamdanesti; Hafni Bachtiar; Syalvia Oresti; Amelia Susanti; Radian Ilmaskal (Green Publisher Indonesia, 2022)
Job satisfaction is the general attitude of an individual towards the work he does. Someone with a high level of job satisfaction shows a positive attitude towards his job, while someone who is dissatisfied with his job shows a negative attitude towards his job. This study aims to examine the factors (age, education, gender, years of service, salary, supervision, working conditions, relations between employees, opportunities for advancement, financial security) that affect nurse job satisfaction. Quantitative research used the study with a cross sectional design. The research instrument is a questionnaire. The study was conducted on June-July, 2017 on 64 nurse respondents at dr. Reksodiwriyo Hospital. Data analysis using Chi-Square and Fisher's Exact. The results showed that only the period of service, working conditions, relationships between employees and financial security were related to job satisfaction, while other factors were not related. It is recommended to improve the factors that affect job satisfaction to maximize the work of nurses.